KONSEP ESTETIKA ALUSAN DAN KASARAN PADA PERHIASAN CINCIN DI KABUPATEN JEPARA - Mohammad Ubaidul Izza (Institut Seni Indonesia Surakarta, 2022)
This paper attempt to construct an aesthetic concept that is stored behind the Alusan predicate as justification the beauty of ring jewelry in Jepara. The revealing uses ethnoart paradigm to trace at once gather Craftsmen’s knowledge about the aesthetic parameters of ring jewelry. The operational uses ethnographic method that focused on participant observation and interview techniques. The research result shows that the concept of aesthetic of alusan was built by three interrelated aesthetic criteria. The parameter evaluation of aesthetics alusan is seen by fulfilled criteria Apik as evaluation of quality crafting, criteria Pantês as matching evaluation between ring shape with gemstones also user, and criteria pénak as comfortable evaluation by indicator user.